Hierarchical three-dimensional Fe3O4@porous carbon matrix/graphene anodes for high performance lithium ion batteries. (10th January 2018) - Hao, Shiji; Zhang, Bowei; Wang, Ying; Li, Chaojiang; Feng, Jianyong; Ball, Sarah; Srinivasan, Madhavi; Wu, Junsheng; Huang, Yizhong
Abstract: In the present paper, the hierarchical three-dimensional Fe3 O4 @porous carbon matrix (PCM) and Fe3 O4 @PCM/graphene are synthesized by a facile annealing of Mil-53(Fe) templates. Their electrochemical performances are evaluated as anode materials for lithium ion batteries. In comparison with Fe3 O4 @PCM, the Fe3 O4 @PCM/graphene electrode exhibits a much better cycling performance with the reversible capacity high up to 1000 mAh g −1 after 500 cycles at 1 C. The improved performance can be ascribed to the high conductivity and structure stability provided by the unique graphene based hierarchical three-dimensional nanostructure.